Realisation of high temperature electronics packaging technology for sensor conditioning and processing applications - Riches, S; Johnston, C; Lui, A (2012)
The requirement to install electronic power and control systems in high temperature environments in aeroengines and in down-well exploration has posed a challenge to the traditional limit of 125°C of electronics systems. The leap in operating temperature to above 200°C in combination with high pressures, vibrations and potentially corrosive environments means that different semiconductors, passives, circuit boards and assembly processes will be needed to fulfil target performance specifications. Silicon on Insulator (SOI) device technology has been shown to be capable of functioning satisfactorily at operating temperatures of >200°C. Most of the applications to date have required performance for short times (<2,000 hours) at the highest operating temperatures of up to 225°C in down-well drilling applications. There is interest in extending the endurance of high temperature electronics into aero-engine and other applications where a minimum 20 year operating life is stipulated. Most of the reliability data on the high temperature endurance of the integrated circuit is generated with little consideration of the packaging technologies, whilst most of the reliability data pertinent to high temperature packaging technologies uses test pieces, which limits any conclusions relating to long term electrical performance. This paper will present results of studies on high temperature packaging technologies relevant to signal conditioning and processing functions for sensors in down-well and aero-engine applications. Different die attach and wire bond options have been included in the study and the performance of several functional blocks on a high temperature SOI device has been tracked over the endurance tests which have lasted for >11,000 hours at 250°C. Degradation phenomena such as thermal migration and material deterioration due to high temperature exposure in air and inert atmospheres will be described. An assessment of the availability of high temperature materials and components to meet long term requirements for operation at 250°C will be presented.